Analysis of Factors that Influence Job Satisfaction on Employee Performance - Pahlevi, Mohd Reza; Afnina, Afnina (Journal Of Accounting Management Business And International Research, 2024)
The aim of the research is to find out whether job satisfaction factors such as remuneration, workload, and leadership attitudes influence employee performance simultaneously and partially. The type of research is quantitative by distributing questionnaires to all employees using saturated sampling, totaling 40 people. Data were processed using the t test, F test, and multiple linear regression. It was found that the most dominant factor influencing employee performance was remuneration, characterized by a regression value of 0.592, followed by leadership attitude 0.405, while workload was 0.322. The influence of the three job satisfaction factors is 50.8% and the remaining 49.2% of performance is influenced by other job satisfaction factors which were not studied. It is recommended that companies monitor employee absenteeism levels, workforce turnover, work morale and employee complaints so that companies will get employees who have high job satisfaction and performance. The findings in this research can complement existing theories and can be a reference for BSI KC Langsa 2 in its efforts to improve employee performance.